FAKTOR PENYEBAB KENAKALAN REMAJA DI NAGARI TARAM KECAMATAN HARAU KABUPATEN LIMA PULUH KOTA SUMATERA BARAT - Nurjanah, Siti; Maemunaty, Titi; Widiastuti, Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine the causes of juvenile delinquency in Nagari Taram, Harau Sub-District, Lima Puluh City, West Sumatra. This study uses a descriptive method with a quantitative approach. The sample in this study was 75 people, namely adolescents who were in Nagari Taram with a random sampling technique using the slivin formula. The technique to collect data using a questionnaire. Techniques for data analysis using the percentage formula. The results of this study indicate that the factors of the self are quite high, the factors of the family are quite high, the factors of the community are classified as moderate.Key Words: Causes, Juvenile Crime In Nagari Taram.